2022
DOI: 10.3390/children9111772
|View full text |Cite
|
Sign up to set email alerts
|

Condylar Asymmetry in Children with Unilateral Posterior Crossbite Malocclusion: A Comparative Cross-Sectional Study

Abstract: Unilateral posterior crossbite (UXB) is a common, severely asymmetric malocclusion, characterized by maxillary hypoplasia and masticatory dysfunction. The aim of this research is to evaluate the asymmetry of mandibular condyles and rami in children with UXB. This comparative cross-sectional study included 33 children with UXB (girls = 15, boys = 18; mean age ± SD = 8.0 ± 1.3 years.months]) and 33 age- and gender-matched controls (girls = 15, boys = 18; mean age ± SD = 8.4 ± 1.3 years.months]). Pre-treatment OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Similar to Kilic's study, Tortarolo et al observed a condylar asymmetry index (CAI) in children with a high value in unilateral reverse occlusion, but these studies only investigated unilateral posterior crossbite compared to the control group with normal occlusion [49]. The novelty of our study comes from the fact that classification was made by classes of malocclusions, including in the study, in addition to UPC, the malocclusions from Angle's classification: Class I, Class II/1, Class II/2 and Class III.…”
Section: Discussionmentioning
confidence: 86%
“…Similar to Kilic's study, Tortarolo et al observed a condylar asymmetry index (CAI) in children with a high value in unilateral reverse occlusion, but these studies only investigated unilateral posterior crossbite compared to the control group with normal occlusion [49]. The novelty of our study comes from the fact that classification was made by classes of malocclusions, including in the study, in addition to UPC, the malocclusions from Angle's classification: Class I, Class II/1, Class II/2 and Class III.…”
Section: Discussionmentioning
confidence: 86%
“…Prolongation of posterior crossbite can cause permanent changes in bony support, and possibly in the growth center at the TMJ, showing that malocclusions, especially transverse anomalies, have a marked effect on mandibular condyle morphology [ 23 , 24 ]. Patients with bilateral posterior crossbite have asymmetrical condyles that might be at risk for the development of future skeletal mandibular asymmetries [ 25 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is important to underline the results of recent research on the cranial structure and condylar asymmetry checked on panoramic X-rays. In patients with RA, compared to a healthy adult control group, the condyles showed a bilateral asymmetry in RA patients due to the high turnover of this joint reacting to severe systemic inflammation [33]. So, it is pivotal to diagnose TMJ early and monitor it in conditions of arthritis, not only assessing the signs and symptoms revealed by patients but also evaluating predictors through additional serological and instrumental exams.…”
Section: Discussionmentioning
confidence: 99%